Enhancing dairy productivity through best bet feeding interventions under smallholders in the central highlands of Ethiopia - Ashagrie, Aemiro K.; Feyissa, Fekede; Kebede, Gezahegn; Faji, Mulisa; Mohammed, Kedir; Mengistu, Gezahegn; Kitaw, Getu; Dejene, Mesfin; Geleti, Diriba; Minta, Muluneh; Rios, Esteban F.; Balehegn, Mulubrhan; et al. (Frontiers in Animal Science, 2023)
Dairy cattle production is an integral part of smallholder farming systems in the central highlands of Ethiopia, but it is characterized by low milk productivity mainly due to nutritional constraints. This study assessed the comparative advantage of using improved forage-based feeding system over the traditional feeding practices on feed intake, milk yield and quality, and cost benefit analysis of crossbred dairy cows under smallholder farmers. The study was conducted at Welmera and Ejere districts on 12 farmers and two cows per farmer, and two dietary treatments were assigned to each cow randomly, and the study lasted 8 weeks. The treatments were: 1) intervention diet composed of oats-vetch mixture hay with concentrate supplementation at the rate of 0.5 kg/l of milk and 2) basal diet following farmers’ current feeding practices: crop residues and native hay, commonly soaked with local brewery residue (“Atela”) and water.. The results showed that there was no difference in total dry matter intake between the two diets. However, the basal feed intake was higher in the traditional feeding practice by 11% whereas the concentrate intake was higher in the intervention diet by 25%. Crude protein intake was significantly higher (P<0.05) in the intervention group by 23%. As a result, milk yield was increased by 36% under oat-vetch mixed fodder-based feeding system as compared to the traditional feeding practice. Consequently, the amount of feed required per unit of milk was lower in the intervention group, indicating higher feed conversion efficiency as compared to the traditional feeding practice. On the other hand, there was no significant variation in milk composition between the two groups. Partial budget analysis indicated that the benefit from the intervention diet (95 birr/cow/day) was greater by 266% than that obtained from the traditional practice (45 birr/cow/day). Utilization of improved forage varieties was proven to play significant role in supplying good quality and abundant feed resource that increased milk yield and also fetch additional economic return for smallholder farmers compared to the existing traditional practice.